Major powers' nuclear policies and international order in the 21st century 2009 NIDS International Symposium on Security Affairs. (National Institute for Defense Studies, 2010)
This is a report of the proceedings of the 12th International Symposium on Security Affairs hosted by the National Institute for Defense Studies (NIDS) on 18 November 2009.